In the zone: New Zealand's legislation for a system of school choice and its effects. (1st July 2005) - Pearce, Diane; Gordon, Liz
Abstract : This paper examines the legislative framework developed in New Zealand over the last 15 years to facilitate greater parental choice in education. The discussion is set within the context of changes to admission practices in a number of education systems to advance the privatisation agenda, and outlines the resurgence of interest in the development of voucher-based models of school choice. The New Zealand case study describes the series of regulatory changes that governed admissions and selection from 1989 onwards, with particular focus on selection in situations of school over-subscription.